El Currículum educacional como campo epistemológico de la Educación: su construcción mediante investigación en el aula - Gedda-Muñoz, Relmu; Guerrero-Azócar, Rafael (Universidad de Costa Rica, 2021)
The present essay aims to problematize the epistemological condition of Education as a constitutive branch of social studies as well as existing on a particular and distinctive field of knowledge. In order to achieve this goal it is proposed, for the Chilean case, the educational curriculum as a particular and essential knowledge of education, arguing that is the object of knowledge belonging to that discipline and therefore requires to be built from its own situational problems to articulate its dilemmas and solutions. With the objective of going further and deeper into the conceptual and methodological structure of the field of Education, so as to strengthen its position as a science, it is stated that classroom research emerges as a strategy to validate the teaching and students' experience to justify the importance of the educational curriculum. In the analysis of the different concepts of educational curriculum, it opts for that proposition that understand the curriculum as a permanent process of building the proper conditions to advocate for the subjects' emancipation, considering the idea of the third included and the ecology of knowledge as validating instances for its design and implementation. As a conclusion, it is established that educational curriculum prepared based on empirical evidence of the educational activity itself, that is, through classroom research, allows to consider Education as a science, actively considering the experience of teachers and students, in an expansice, free and emancipated environment, over the strict disposition of governments and standardized curriculum.